Distribution features of the red squirrel (Sciurus vulgaris) in the south of Ukraine: a case study of Mykolaiv Oblast - Kostiantyn Redinov (Theriologia Ukrainica)
Until recently, the natural geographic range of the red squirrel (Sciurus vulgaris) has not covered the area of Mykolaiv Oblast, as opposed to Podillia and the forest-steppe belt of Ukraine. Over the past 40 years, due to artificial and natural dispersal, this dendrophilous rodent species has significantly expanded in range into Mykolaiv Oblast, 93% of which is located within the steppe and 7% within the forest-steppe zones of Ukraine. The squirrels moved from the forest-steppe zone, from the city of Kryvyi Rih and along the Dnipro valley. The dispersal has been gradual, took place in waves, and has become widespread in the last 10–15 years. In the city Pervomaisk on the river the species was observed for the first time in Southern Bug in 1980, in the northeast of the region in 2002, near the city of Mykolaiv — 1997. On the Kinburn Peninsula, the squirrel first appeared as a result of artificial introduction in the 1980s in the adjacent territory of Kherson Oblast. In the 21st century, other subspecies also dispersed naturally into the region along the Dnipro River valley and are now widespread here together with descendants of the ‘common’ and teleutka squirrels. The animals appeared in Ochakiv as a result of introduction in 2020. As of 2024, the squirrels are widespread within the northern steppe subzone of the steppe zone and locally within the middle steppe and dry steppe subzones of the steppe zone. The species is more widespread than scientists considered. The squirrel’s distribution was facilitated by forest reclamation, in particular the planting of forest belts and walnut orchards and other plantations, as well as by its ecological plasticity, introduction, synanthropisation, and the loyal attitude of the majority of the population to the species. In some places, the animals have established themselves and started breeding, such as in the cities of Novyi Buh, Mykolaiv, and Pervomaisk, and also in forest tracts, etc. The species’ natural enemy is the Eurasian goshawk (Accipiter gentilis). According to the available data, in Mykolaiv Oblast, there are red squirrels from natural populations of the forest-steppe and Podillia of Ukraine, introduced teleutka squirrels, and probably their hybrids as well. As of 2020–2024, the estimated abundance of squirrels in the territory of Mykolaiv Oblast is approximately 250–500 individuals.